2021
DOI: 10.1111/ane.13480
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure variability following endovascular thrombectomy and clinical outcome in acute ischemic stroke: A meta‐analysis

Abstract: Blood pressure variability (BPV) has been linked with the outcome of acute ischemic stroke (AIS) after endovascular thrombectomy (EVT). However, the association of the stroke outcome with specific short‐term BPV parameters is unclear. We did a systematic literature search for studies published from January 2010 to September 2020. Eligibility criteria included studies with (1) AIS patients treated with EVT with or without thrombolysis; and (2) analysis of the association between short‐term systolic BPV paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Nepal et al pointed out that patients with a large coefficient of variation in blood pressure had a greater pressure on the vascular endothelium of the collateral circulation, which would more easily accelerate bleeding and affect the prognosis. [ 18 ] In addition, Kolyviras et al suggested that patients with large variations in blood pressure levels might increase shear force in the vasculature by upregulating endothelial cytokines, thereby inducing vascular inflammation, destroying the blood–brain barrier, promoting the formation of atherosclerotic plaques, and destroying the prognosis. [ 19 ] In addition, increased BPV can impair cerebral autoregulation in acute ischemic brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Nepal et al pointed out that patients with a large coefficient of variation in blood pressure had a greater pressure on the vascular endothelium of the collateral circulation, which would more easily accelerate bleeding and affect the prognosis. [ 18 ] In addition, Kolyviras et al suggested that patients with large variations in blood pressure levels might increase shear force in the vasculature by upregulating endothelial cytokines, thereby inducing vascular inflammation, destroying the blood–brain barrier, promoting the formation of atherosclerotic plaques, and destroying the prognosis. [ 19 ] In addition, increased BPV can impair cerebral autoregulation in acute ischemic brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Every 5-mmHg increase in the pulse pressure variability was related to a 36% decrease in the likelihood of independent functional outcome and a 60% increase in the odds of mortality at three months of stroke onset [ 18 ]. Furthermore, a meta-analysis suggests that systolic BPV measurements during the first 24 h after EVT, including SD, CV, and successive variation, is indicative of clinical outcome at three months of stroke onset [ 19 ]. Therefore, maintaining less BPV at 24-h stage, relative to other stages, is particularly essential in promoting better clinical outcome in AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Despite successful recanalization via MT, some patients develop early neurological deterioration (ND). An increase in ⩾4 points of the National Institutes of Health Stroke Scale (NIHSS) between pretreatment and Day 1 is commonly considered as an early ND, 1 4 though for minor stroke patients an increase in ⩾2 points of the NIHSS is considered as ND. 1 5 Several studies demonstrated that early or subacute ND is a strong predictor of poor stroke outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in ⩾4 points of the National Institutes of Health Stroke Scale (NIHSS) between pretreatment and Day 1 is commonly considered as an early ND, 1 4 though for minor stroke patients an increase in ⩾2 points of the NIHSS is considered as ND. 1 5 Several studies demonstrated that early or subacute ND is a strong predictor of poor stroke outcomes. 6 Apart from obvious causes such as lack of recanalization, parenchymal hemorrhage, malignant edema, or procedural complications, ND might remain unexplained in over half of cases (UnND).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation